2013
DOI: 10.1302/0301-620x.95b1.29565
|View full text |Cite
|
Sign up to set email alerts
|

Early results of a remotely-operated magnetic growth rod in early-onset scoliosis

Abstract: Conventional growing rods are the most commonly used distraction-based devices in the treatment of progressive early-onset scoliosis. This technique requires repeated lengthenings with the patient anaesthetised in the operating theatre. We describe the outcomes and complications of using a non-invasive magnetically controlled growing rod (MCGR) in children with early-onset scoliosis. Lengthening is performed on an outpatient basis using an external remote control with the patient awake.Between November 2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
3
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 29 publications
6
106
3
10
Order By: Relevance
“…There is very little published literature on the use of MAGEC as a revision procedure; however, comparing our results for MAGEC performed as a primary procedure, or results for correction and control are comparable. For example, Dannawi et al [8] recently reported 32 % improvement in Cobb angle, compared with our initial correction of 43 %. Akbarnia et al [3] also found a 43 % improvement in Cobb angle following surgery in 14 patients who had MAGEC performed as a primary procedure [3,8] and Cheung et al [7] found 57 % correction.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…There is very little published literature on the use of MAGEC as a revision procedure; however, comparing our results for MAGEC performed as a primary procedure, or results for correction and control are comparable. For example, Dannawi et al [8] recently reported 32 % improvement in Cobb angle, compared with our initial correction of 43 %. Akbarnia et al [3] also found a 43 % improvement in Cobb angle following surgery in 14 patients who had MAGEC performed as a primary procedure [3,8] and Cheung et al [7] found 57 % correction.…”
Section: Discussionsupporting
confidence: 41%
“…Patients had rod extensions in clinic every 6-8 weeks. Scoliograms were performed on average 11 times per year (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] In order to minimize the limitations of traditional growing rod systems magnetically-controlled growing rods (MCGR) were developed, and their safety and efficacy has been reported in humans. [10][11][12][13] . Their implantation is supported following a clinical and economical evaluation by the National Institute of Clinical Excellence in the United Kingdom as part of an evidence medical technologies guidance.…”
Section: Introductionmentioning
confidence: 99%